Ninja hacking unconventional penetration testing tactics and techniques - Wilhelm, Thomas (Syngress/Elsevier, 2011)
Ever thought of using the time-tested tactics and techniques of a ninja to understand the mind of today's ninja, the hacker? As a penetration tester or security consultant you no doubt perform tests both externally and internally for your clients that include both physical and technical tests. Throw traditional pen testing methods out the window for now and see how thinking and acting like a ninja can actually grant you quicker and more complete access to a company's assets. Get in before the hacker does by thinking outside of the box with these unorthodox techniques. Use all of the tools that the ninja has at his side such as disguise, espionage, stealth, and concealment. Learn how to benefit from these by laying your plans, impersonating employees, infiltrating via alarm system evasion, discovering weak points and timing, spyware and keylogging software, and log manipulation and logic bombs. And, really, don't you want to be a ninja for a day just because they're cool? Let this book be your excuse! Use the tactics of a ninja such as disguise, espionage, stealth, and concealment to protect your company's assets Details unorthodox penetration testing techniques by thinking outside of the box and inside the mind of a ninja Expands upon current penetration testing methodologies including new tactics for hardware and physical attacks.